Internalizing Knowledge and Changing Attitudes to Female Genital Cutting/Mutilation - Inger-Lise Lien; Jon-Håkon Schultz (Obstetrics and Gynecology International)
The process of paradigmatic attitudinal change has been analyzed by the use of multimethods and multileveled internalization theories. Forty-six informants (a network of activists and a group of Gambian women) have described their change of attitude to female genital cutting. This study shows that internalizing a packet of information as adults, that contradicts an old schema of knowledge internalized as children, can be experienced as epistemologically very painful. Activists in Norway who have changed their attitude to FGC have got information from different educational institutions, from seminars and conferences, from work as interpreters in hospitals, and from discussions among families and friends. Information can be received, listened to and subsequently discarded. In order to design FGC-abandonment campaigns, the importance of the internalization process in order for the individual to make an attitudinal change must be understood.